Biomechanical modelling as a method of studying athlete's motor actions - Ilia Vako (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
Topicality. One of the common methods of biological objects study is modelling. Using basic laws of physics, mechanics, mathematics, biology, physiology and other sciences, this method allows explaining the functional structure of the studied process, identifying its significant connection with external objects, internal organization, and evaluating quantitative characteristics. The model is referred as to such a mentally represented or materially realized system, which, reflecting or reproducing the object of study, is able to replace it so that its study gives new information about this object. The search for an analogue for the original is possible on the basis of the following types of models as deterministic models, i.e. models based on systems of algebraic, regression and differential equations, equations in partial derivatives; statistical models that predict the probability of various events. The task of the research is to conduct a comparative biomechanical analysis of a side kick performing technique at close reach by athletes of different qualification who specialize in hand-to-hand combat and on this basis to determine the model characteristics of sport technique. Research methods. To achieve the set tasks, we have applied such research methods as analysis of scientific and methodological literature as well as documentary materials, methods of registration and analysis of athlete's movements (system of video recording and analysis of athlete's movements, 3D recording of human movements "Qualisys Motion Capture"). The results obtained during the study have been processed with the help of mathematical statistics methods. Results of the research. It should be noted that the surveyed skilled athletes who specialize in hand-to-hand combat do not apply a preparatory phase of acceleration, as it is characteristic for highly skilled athletes. After the initial position, qualified athletes perform a forward movement in the course of a future blow. For highly skilled athletes a counter-movement is typical - first backwards (that increases the path and creates the conditions for clearer twisting), afterwards there are a few moments of movement forward with active pelvis movement thus overtaking the shoulder axis by the pelvic axis. Conclusions. Highly skilled athletes have a fairly high consistency of the inclusion of individual bio-links when performing a side hook with the help of the hand at close reach. At the same time, a slight advance of the elbow joint maximum speed at the time of strike indicates the need for further work on the technique of masters of sports. Significant reserves in this regard are available to qualified athletes, namely there is usually no preliminary phase associated with the pelvis and shoulder joint movements of the athlete who beats back after taking the initial position (in strike actions this phase is called swing or propulsion); there is an inconsistent inclusion of individual bio-links in the work, as evidenced by the dynamics of changes in the resulting rate of individual bio-links.